2021
DOI: 10.1155/2021/8847698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Melatonin on the Quality of Soybean and Natto Products under Drought Stress

Abstract: Melatonin can directly or indirectly eliminate reactive oxygen species, regulate hormone levels, and improve drought-stressed soybean crop resistance, yield, and quality. The nutrient contents of soybeans grown under normal conditions (WW), drought stress (D), and drought stress with exogenous melatonin (D + M) ( p < 0.05 ) were compared. The differences in the quality of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[56,76]. Melatonin is also an antioxidant that protects plants from biotic and abiotic stresses [38,77], such as salt [41,78], drought [79][80][81], cold [59,82], and heavy metal stress [7]. Melatonin application reduced stress-induced photosynthetic inhibition (Table 2), suggesting that the overall lnRR ++ of total chlorophyll, chlorophyll a and b, and carotenoid were 18, 38, 24, and 18% higher than control, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[56,76]. Melatonin is also an antioxidant that protects plants from biotic and abiotic stresses [38,77], such as salt [41,78], drought [79][80][81], cold [59,82], and heavy metal stress [7]. Melatonin application reduced stress-induced photosynthetic inhibition (Table 2), suggesting that the overall lnRR ++ of total chlorophyll, chlorophyll a and b, and carotenoid were 18, 38, 24, and 18% higher than control, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The sugars in tomato fruit are mainly fructose, glucose, and a small amount of sucrose [ 42 ]. Previous studies have shown that exogenous melatonin improves the yield and quality of soybean by promoting the accumulation of photosynthetic products, such as sucrose, starch, glucose, and fructose [ 15 ]. In our study, the content of fructose in tomato fruit at 48 d after anthesis was increased by melatonin treatment ( Figure 1 A) and glucose content at 34 d ( Figure 1 B), but melatonin treatment increased sucrose content in tomato fruit as early as 27 d ( Figure 1 C).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have reported that melatonin can also regulate the appearance, quality, and nutrition of the fruit. For instance, the contents of starch, sucrose, fructose, glucose, and protein in soybean treated with melatonin significantly increased [ 15 ]. After irrigating the exogenous melatonin solution [ 16 ], the contents of ascorbic acid, lycopene, soluble solids, and phosphorus in tomato fruit were found to be enhanced compared to the control [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most distinctive feature of natto is that its surface is covered with white viscous material, which can form mucus after stirring. High-quality natto mucus is white, with a light or slightly sour smell, light yellow color, and soft and sticky texture, which has become an important criterion for judging high-quality natto (Yoshikawa et al, 2014;Cao et al, 2021;Wei & Chang, 2004). The stickiness and drawing properties of natto mucus are due to the strong viscous poly-γ-glutamic acid (γ-PGA) and levan, which have a stabilizing effect (Yoshioka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because food evaluations are based on psychological rather than field or laboratory factors, sensory evaluation is necessary (Yoshikawa et al, 2014). In the sensory experiments of natto, the drawing performance of mucus is mostly used as the measurement standard (Cao et al, 2021;Yoshikawa et al, 2014;Yang et al, 2021). In a sensory test aimed at the elderly in Tokyo, participants rated soft, sticky natto as better than what they generally believed to be natto, and a newly developed soft, sticky natto proved to be useful as food for the elderly (Mitsuboshi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%